2021
DOI: 10.1007/s10815-021-02222-0
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte cryopreservation versus ovarian tissue cryopreservation for adult female oncofertility patients: a cost-effectiveness study

Abstract: Purpose In December 2019, the American Society for Reproductive Medicine designated ovarian tissue cryopreservation (OTC) as no longer experimental and an alternative to oocyte cryopreservation (OC) for women receiving gonadotoxic therapy. Anticipating increased use of OTC, we compare the cost-effectiveness of OC versus OTC for fertility preservation in oncofertility patients. Methods A cost-effectiveness model to compare OC versus OTC was built from a payer perspective. Costs and probabilities were derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…107 Firstly, gamete cryopreservation (or embryo freezing) has a low return rate, making it a relatively expensive option. 87,107 The current estimate suggests that only around 5% of patients who preserve their embryos or oocytes actually return to the fertility unit to use them. In order to achieve cost-effectiveness, this return rate would need to be increased to more than 60%.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…107 Firstly, gamete cryopreservation (or embryo freezing) has a low return rate, making it a relatively expensive option. 87,107 The current estimate suggests that only around 5% of patients who preserve their embryos or oocytes actually return to the fertility unit to use them. In order to achieve cost-effectiveness, this return rate would need to be increased to more than 60%.…”
Section: Methodsmentioning
confidence: 99%
“…It would require a return rate of more than 80% to meet the criteria for cost-effectiveness. 107 However, careful patient selection, especially targeting individuals at risk of premature menopause, can result in higher return rates. 108 OTC offers the advantage of minimising the need for Hormonal Replacement Treatment and has shown high live birth rates through both assisted and natural conception.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These estimated costs include 1 year of storage, with additional storage costing an average of $343/year [54]. Should patients use the cryopreserved tissue to conceive, the cost increases: a 2020 study of women who underwent cryopreservation prior to gonadotoxic chemotherapy found that when the cost of thaw and fertilization cycles and frozen embryo transfer was included, the total cost of a successful pregnancy with cryopreserved oocytes averaged $16,588 [55].…”
Section: Financial Barriersmentioning
confidence: 99%
“…Moreover, OTC provides the opportunity to preserve hundreds of primordial follicles at once ( Lotz et al , 2019 ), thereby not restricting women to a finite number of oocytes cryopreserved, which is a known limitation of EOC. Interestingly, a recent cost-analysis study of women undergoing onco-fertility treatment in America, demonstrated that OC was more costly than OTC ($16 588 versus $10 032, respectively) ( Chung et al , 2021 ). In a prospective study comparing the efficacy of oocyte vitrification vs OTC in women undergoing gonadotoxic treatments, higher LBRs per patient were observed in the OC group, although there was no statistical significance between the groups (32.6% versus 18.2%, respectively) ( Diaz-Garcia et al , 2018 ).…”
Section: Elective Ovarian Tissue Cryopreservationmentioning
confidence: 99%